A Cognitive Semantic Analysis of Selected American Political Caricatures on Covid 19 - Ikhlas Mahdi Hasan; Ayad Hameed Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Political caricatures are reflections of real situations or affairs that are summarized through drawings. Recently, they have become key elements in political communication since they manipulate different verbal and visual elements in shaping the political messages and attracting the recipient's attention. These different modes include verbal and visual elements. Accordingly, they provide a new framework to understand political discourse. This paper is an attempt to examine the efficiency of Langacker’s (2008-2017) construal dimension of prominence to the analysis of visual and verbal elements of political caricatures. It aims to prove that the prominence parameters of profiling and trajectory/ landmark alignment can account for the phenomenon of multiple construal triggered by visual and verbal modes, and the process of meaning construction in political caricatures. To achieve these aims, a sample of American political caricatures published on Covid 19 has been selected to be analyzed. Analysis of the selected data shows that the semantic content of the political cartoons resides on the visual and verbal elements employed in these caricatures. Both types of elements highly depend on Langacker’s two construal parameters of prominence, profiling and trajector/landmark, in constructing and conveying their intended messages. In addition, the way the conceptualizers construe the scenes participates greatly to decoding these messages.